2003
DOI: 10.1086/368205
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofUreaplasma urealyticumin Second‐Trimester Amniotic Fluid by Polymerase Chain Reaction Correlates with Subsequent Preterm Labor and Delivery

Abstract: Ureaplasma urealyticum is the microorganism most frequently isolated from the amniotic fluid of women in preterm labor. The relationship between intra-amniotic U. urealyticum in healthy second-trimester pregnant women and subsequent pregnancy outcome was investigated. Transabdominal amniotic fluid obtained from 254 asymptomatic women at 15-17 weeks' gestation were tested by polymerase chain reaction (PCR). U. urealyticum was identified in 29 subjects (11.4%). A subsequent preterm labor occurred in 17 U. urealy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(132 citation statements)
references
References 15 publications
4
125
0
3
Order By: Relevance
“…Preterm labour was not a consequence of amniotic fluid ureaplasma colonization. The majority of normal human pregnancies that had amniotic fluid that was PCR positive for Ureasplama at 15-18 weeks gestation also did not deliver prematurely (7,17). Despite the presence of ureaplasmas in the lungs of late gestation lambs and persisting effects on lung development, as indicated by increased surfactant lipid content of 145d lambs, lung function in late gestation was not affected.…”
Section: Discussionmentioning
confidence: 97%
“…Preterm labour was not a consequence of amniotic fluid ureaplasma colonization. The majority of normal human pregnancies that had amniotic fluid that was PCR positive for Ureasplama at 15-18 weeks gestation also did not deliver prematurely (7,17). Despite the presence of ureaplasmas in the lungs of late gestation lambs and persisting effects on lung development, as indicated by increased surfactant lipid content of 145d lambs, lung function in late gestation was not affected.…”
Section: Discussionmentioning
confidence: 97%
“…However, no significant differences in perinatal outcome were observed between patients with a negative culture but positive PCR and those with a positive amniotic fluid culture (342). Another recent study (93) found that preterm labor occurred in 58.6% women with a positive PCR assay for ureaplasmas at 15 to 17 weeks of gestation compared with only 4.4% of women with negative PCR results, suggesting the potential value of PCR testing of second trimester amniotic fluid to identify women at risk for preterm labor and delivery.…”
Section: Chorioamnionitis Spontaneous Abortion and Preterm Labormentioning
confidence: 91%
“…Ureaplasma has been implicated in infertility, spontaneous abortion, stillbirth, premature birth, low birth weight, and perinatal morbidity and mortality (3). Vaginal colonization with Ureaplasma has not been associated with preterm birth (3), while the presence of Ureaplasma in the amniotic fluid is associated with a robust host response in fetal, amniotic, and maternal compartments (24) and subsequent preterm birth (7). It is not known why this microorganism invades the amniotic cavity only in some women despite heavy colonization of the vagina by Ureaplasma.…”
mentioning
confidence: 99%
“…Therefore, U. urealyticum organisms examined in previous studies (3,7,24) may have included both U. parvum and emended U. urealyticum. It is possible that the two new Ureaplasma species differ from each other in pathogenicity, as suggested in several studies (1,18).…”
mentioning
confidence: 99%